A DESCRIPTIVE STUDY OF ‘KO’ IN KUPANG MALAY - Edron Natu Obe Sa'u (Academic Journal of Educational Sciences, 2018)
This thesis is entitled “A Descriptive Study of ‘Ko’ in Kupang Malay”. The method used in this research is descriptive qualitative to answer the questions (1) what is the morphological status of ‘ko’ in Kupang Malay?, (2) what is the meaning of ‘ko’ in Kupang Malay?, (3) what are the functions of ‘ko’ in Kupang Malay?. The aims of this research are to find out the morphological status of ‘ko’ in Kupang Malay, to know the meaning of ‘ko’in Kupang Malay, and to know the functions of ‘ko’ in Kupang Malay. The techniques to collect the data were observation, interview and note taking. After doing the observation, the writer analyzed the data and the result shows that the morphological status of ‘ko’ in Kupang Malay is a free morpheme because it is capable of standing alone as a complete word. The word ‘ko’ can be a content words namely as an adverb, and it can also be function word, functioning as conjunction and interrogative word. The meaning of ko as an adverb are about, maybe, perhaps, probably and just, the function of ko as an adverb is to modify another adverb and verb. The meaning of ko as conjunction are or, because, if, and so that, the function of ko as conjunction is to conjoin two independent clauses. The meaning of ko as interrogative words is as a Yes-No question words; those question beginning with an auxiliary verb and to be, the function of ko as interrogative word is to ask question and require Yes or No as the answer.